2009
DOI: 10.1007/s11528-009-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Labels DO Matter! A Critique of AECT’s Redefinition of the Field

Abstract: AECT has recently (yet again!) redefined our field, reverting back to the use of the term educational technology. We believe this recent change is problematic for a number of reasons, but primarily because of the weak rationale offered for the change. This change affects how external audiences view our profession and is likely to confuse practitioners in corporate and higher-ed settings in particular. We offer a review of job postings, program titles, and listserv discussions to support our case. The labels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 15 publications
(13 reference statements)
0
21
0
2
Order By: Relevance
“…Now, social presence appears as a form of effectiveness, efficiency and satisfaction in using of communication media [17]. Specifically, Lowenthal and Wilson [18] states that social presence is people"s perception of a person"s being real. It means that people set up themselves in the environment and others can perceive them.…”
Section: Social Presencementioning
confidence: 99%
“…Now, social presence appears as a form of effectiveness, efficiency and satisfaction in using of communication media [17]. Specifically, Lowenthal and Wilson [18] states that social presence is people"s perception of a person"s being real. It means that people set up themselves in the environment and others can perceive them.…”
Section: Social Presencementioning
confidence: 99%
“…Didaktické znalosti obsahu (z anglického pedagogical content knowledge) jsou speci ické znalosti, které spočívají v učitelově schopnosti transformovat obsah "do forem, které jsou pedagogicky účinné, a přesto přizpůsobivé schopnostem žáků" (Shulman,1987, s. 15 Konstrukční výzkum je systematická a lexibilní metodologie zaměřená na zdokonalení vzdělávací praxe prostřednictvím iterativní analýzy, designu, vývoje a implementace vzdělávacích intervencí, založená na aktivní spolupráci výzkumníků, praktiků a žáků v přirozeném prostředí, která vede k produkci konstrukčních principů a nových teorií (Amiel & Reeves, 2008;Barab & Squire, 2004;Plomp & Nieveen, 2013a;Van der Akker, 2006 V anglickém jazyce se termín educational technology používá jak pro praktické využití, tak i jako označení pro teoretický rámec a směr přemýšlení o tom, jak pomocí technologií vhodně vzdělávat, tedy ne pouze pro fyzickou aplikaci technologií do kurikula (Lowenthal & Wilson, 2010).…”
Section: Dualistický Charakter Konstrukčního Výzkumuunclassified
“…For our study we chose to use the Association for Educational Communications Technology (AECT) as the main professional organization for IDT. Lowenthal and Wilson (2009) argued that ''AECT historically has been uniquely influential in shaping and guiding theory and practice of instructional design and technology'' (p. 39), and Lowenthal (2012) surveyed 140 instructional design and technology professionals recruited through the ITFORUM listserv on which conferences they attend, and found that AECT was the most frequently attended conference (attended by 50 of the respondents, with Educause second at 33 and AERA third at 32).…”
Section: Professional Awards Selectionmentioning
confidence: 99%